The burden of travelling for cervical cancer treatment in Uganda:A mixed-method study - Dau, Hallie; Zhou, Chuanlin; Nankya, Esther; Naguti, Priscilla; Basemera, Miriam; Payne, Beth A.; Vidler, Marianne; Singer, Joel; McNair, Avery; AboMoslim, Maryam; Mithani, Nadia; Smith, Laurie; et al. (Blackwell Publishing Ltd, 2024)
Background Uganda has one of the highest rates of cervical cancer in the world. Many women are diagnosed and treated with advanced stages of the disease. With only one facility offering comprehensive cervical cancer care in Uganda, many women are required to travel significant distances and spend time away from their homes to receive cervical cancer care. It is important to understand the burden of time away from home while attending treatment because it can inform the expansion of cervical cancer treatment programmes. The aim of this mixed‐methods paper is to describe how the distance to cervical cancer treatment locations impacts women in Uganda. Methods Women were recruited from 19 September, 2022, to 17 January, 2023, at the Uganda Cancer Institute (UCI) and the cancer clinic at Jinja Regional Referral Hospital (JRRF). Women were eligible for the study if they were (i) aged ≥18 years with a histopathologic diagnosis of cervical cancer; (ii) being treated at the UCI or JRRF for cervical cancer; and (iii) able to provide consent to participate in the study in English, Luganda, Lusoga, Luo, or Runyankole. All participants completed a quantitative survey and a selected group was sampled for semi‐structured interviews. Data were analysed using the convergent parallel mixed‐methods approach. Descriptive statistics were reported for the quantitative data and qualitative data using an inductive‐deductive thematic analysis approach. Results In all, 351 women participated in the quantitative section of the study and 24 in the qualitative. The quantitative and qualitative findings largely aligned and supported one another. Women reported travelling up to 14 h to receive treatment and 20% noted that they would spend three or more nights away from home during their current visit. Major themes of the qualitative include means of transportation, spending the night away from home, and financial factors. Conclusion Our findings show that travelling to obtain cervical cancer care can be a significant burden for women in Uganda. Approaches should be considered to reduce this burden such as additional satellite cervical cancer clinics or subsidised transportation options.
Keywords: cervical cancer; mixed-methodology; travel; treatment; Uganda